Estudios cariológicos de cinco especies de serpientes costarricenses de la familia colubridae - Solórzano López, Alejandro (1984)
The karyotypes of five species of colubrid snakes from Costa Rica are as follows: Imuntodes cenchao and Drymobius margaritiferus have a diploid number of 36, with 16 macro- and 20 microchromosomes. The fourth pair is heteromorphic in females of I. cenchoa, with a metacentric Z and a submetacentric W chromosomes. Karyotypes of Erythrolampius bizonus and Leimadophis epinephalus have 28 chromosomes, without a clearcut separation between macro- and microchromosomes. In the case of E. bizomus, the fourth pair contains the sex chromosomes Z and W, both are submetacentric, but the W is smaller. Xenedon rabdocephalus has a diploid number of 34 chromosomes (22 macro- and 12 microchromosomes); pair 3 is heteromorphic in femaJes, with a submetacentric Z and a smaller metacentric W. The karyotype of X. rabdocephalus may be derived from a primitive karyotype by means of reduction in the number of microchromosomes and centric fissions of two pairs of metacentric autosomes.